Revealing Hardiness In Students Migrants (A Study Of Students From Papua In Makassar City) - Ismail, Nur Syamsu; Rustham, Andi Tenri Pada; Sarman, Immanuel Jason Edwardnov (PINISI Discretion Review, 2024)
This study aims to explain what the hardiness personality is like in migrant students, especially migrant students from Papua in Makassar City. This study uses a qualitative method with a theory-driven approach, involving three subjects who were born and grew up in Papua, have undergone a bachelor's degree education process for at least two semesters, and have migrated to Makassar City for at least 1 year. The results of the study showed that the three subjects had a hardiness personality that was reflected through the realization of aspects of control, commitment, and challenge. Other findings obtained from the following study indicate four factors that support the emergence of a hardiness personality, namely academic involvement, reflective thinking skills, self-regulation, and courage. The researcher hopes that the following research areas can be useful for psychology science and also for students who are away from home in developing a hardiness personality.